“Abundantly Worthy of its Past”:: Agnes Maule Machar and Early Canadian Historical Fiction - Fiamengo, Janice (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
While we tend to see the problematizing of history as a distinctly postmodern concern, two of Agnes Maule Machar's (1837-1927) nineteenth-century historical novels, For King and Country (1874) and Marjorie's Canadian Winter (1893), show that even the most (apparently) hegemonic narratives of the period remain concerned with problems of historical representation and the vexed relationship between past and present. Through the process of uncovering certain hidden moral 'truths,' various ethnic, political, and moral tensions of the period that complicated Canada's past— as well as its present— show through. Although Machar never fully subverted contemporary assumptions about history, her attempt to reconcile many of Canada's national conflicts provides a window onto nineteenth century Canada.